2015
DOI: 10.1021/am5076748
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotube Array Photoelectrocatalyst and Ni–Sb–SnO2 Electrocatalyst Bifacial Electrodes: A New Type of Bifunctional Hybrid Platform for Water Treatment

Abstract: Bifunctional hybrid electrodes capable of generating various reactive oxygen species (ROS) over a wide range of potentials were developed by coupling electrocatalysts and photoelectrocatalysts. To achieve this, Ni-doped Sb-SnO2 (NSS) was deposited on one side of a titanium (Ti) foil while the other side was anodized to grow a TiO2 nanotube array (TNA) for electrochemical ozone generation and photoelectrochemical hydroxyl radical generation, respectively. Surface characterization indicated that NSS and TNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 43 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…There into, the phenolic wastewater that includes phenol and 2,4,5-Trichlorophenol (TCP) has been one of the major problems for decades. Phenolic compounds are examples of recalcitrant toxic pollutants presented in liquid waste streams from a variety of industries, such as those involved in production of steel, resins, ceramics, fiberglass, fungicides and herbicides, metals, and textiles [4][5][6]. Especially, 2,4,5-TCP tends to bioaccumulate in the environment due to its biorecalcitrance in nature and in wastewater treatment plants [7].…”
Section: Introductionmentioning
confidence: 99%
“…There into, the phenolic wastewater that includes phenol and 2,4,5-Trichlorophenol (TCP) has been one of the major problems for decades. Phenolic compounds are examples of recalcitrant toxic pollutants presented in liquid waste streams from a variety of industries, such as those involved in production of steel, resins, ceramics, fiberglass, fungicides and herbicides, metals, and textiles [4][5][6]. Especially, 2,4,5-TCP tends to bioaccumulate in the environment due to its biorecalcitrance in nature and in wastewater treatment plants [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a later publication [26] they used ethanol as solvent but kept the high dopant levels in the precursor solution. This resulted in a very low current efficiency for ozone formation of 1 %, whereas 9.3 % was reached when water was used as solvent.…”
Section: Importance Of Preparation Routementioning
confidence: 99%
“…This was later discussed to be a consequence of surface enrichment of Sb [9,14]. Other studies have also reported an enrichment of either Sb or Ni, or both [24][25][26]. Most authors correlate this to surface enrichment.…”
Section: Introductionmentioning
confidence: 97%
“…physisorbed ÁOH (donated as MO x (ÁOH)), which are critical for unselective and effective degradation of organic pollutants [18,20,33]. It has been reported that O ad appears to actively participate in electrochemical reactions [34]. In contrast, TPTM/ATO with a lower O ad content tends to form weak oxidants (e.g.…”
Section: Sem Analysismentioning
confidence: 99%